Neutral and niche‐based factors simultaneously drive seed and invertebrate removal by red harvester ants. (16th February 2021) - Luna, Pedro; García‐Chávez, Juan H.; Izzo, Thiago; Sosa, Vinicio J.; Del‐Claro, Kleber; Dáttilo, Wesley
Abstract : 1. The factors that drive resource removal by insect predators hold the clue to understanding their role in structuring ecological communities and their evolution. Harvester ants are formidable seed predators and invertebrate carcass feeders. However, the extent to which neutral and niche‐based factors drive the selection and removal of preferred food resources by such ants has been neglected in the literature. 2. In this study authors evaluated how the richness of plants and their abundance, along with resource proximity, density, nutrient content, and seasonal changes affect the selective harvest of resources by the harvester ant Pogonomyrmex barbatus in a Neotropical semi‐arid region where resource availability changes across rainy and dry seasons. 3. In accordance with the neutral‐niche theory shaping biotic interactions, the authors observed that P . barbatus more frequently collects the seeds of the most abundant plant species located within their foraging areas, both in the dry and rainy seasons. The authors also observed that resources located in the proximity of nests, and those that are available at high density, are removed more often in the dry, whereas protein‐rich resources located at close range were removed most often in the rainy (i.e. niche‐based factors). Moreover, temporal fluctuations in the collection of seeds and invertebrates by P . barbatus suggest that the phenology of plants is a factor that can affect the availability and collection of resources. 4. The findings exemplify how the dynamics between an insect predator and its food resource can be simultaneously explained by both neutral and niche‐based factors. Abstract : Both neutral and niche‐based factors could explain the selection of resources by the red harvester ant. Pogonomyrmex barbatus more frequently collects resources at high density located in the proximity of nests, whereas protein‐rich resources located at close range were removed most often only in the rainy season. Phenology is a factor that can affect the availability and collection of resources.